How Do Assignment Workload and Time Management Relate to Academic Stress in Early Adolescence? - Khafifatu Syahraini; Nurhayati; Khusnul Fatimah (Women, Education, and Social Welfare, 2026)
Academic stress can undermine adolescents' well-being during the transition to lower secondary education, particularly when assignment demands accumulate within limited completion windows. This cross-sectional correlational study examined the relationships of perceived assignment workload and time management with academic stress among 127 Grade VII students at a public lower secondary school in Kolaka, Indonesia. Data were collected using five-point Likert-scale questionnaires and analyzed through descriptive statistics, Pearson correlations, and multiple linear regression. Assignment workload was positively associated with academic stress (r = 0.363, p < 0.001, 95% CI [0.202, 0.505]). Time management was not significantly associated with stress (r = 0.136, p = 0.127, 95% CI [-0.039, 0.303]). Jointly, the predictors explained 13.2% of the variance in academic stress, F(2,124) = 9.454, p < 0.001. In the regression model, workload was a significant predictor (B = 0.387, p < 0.001), whereas time management was not (B = -0.027, p = 0.758). The findings position assessment coordination and manageable assignment design as human-centered educational priorities. Time-management support remains valuable, but it should complement rather than substitute institutional responsibility for preventing avoidable academic overload.